Sosialisasi hipertensi di lingkungan masyarakat RW 07 Kelurahan Candirenggo: Langkah preventif upaya peningkatan pengetahuan dan kesadaran masyarakat - Syahroni, Moch Ilham (Maliki Interdisciplinary Journal, 2024)
Hypertension is a health problem that is increasing worldwide. The hypertension socialization activity at RW 07 Candirenggo Village aims to increase public awareness of the dangerous risks of this disease so that the community has preventive measures to minimize the risk of hypertension. The method used is in the form of lectures using power point and posters which are distributed to each community as well as questionnaires before and after the socialization. The socialization activity was held on Saturday, January 7 2023 in the Balai RW 07 Candirenggo Village, Singosari District, Malang Regency which was attended by 23 participants. Evaluation of this activity was carried out by analyzing the value of the questionnaire before and after the socialization. The results of hypertension socialization activities show that people's knowledge about hypertension and its prevention efforts has doubled. This is known by increasing the value of the posttest. In addition, the significance value <0.003 indicates that this socialization is effective in increasing public knowledge. It is hoped that this increase in knowledge can be implemented in everyday life as a form of prevention of hypertension and to encourage changes in healthier behavior.